The importance of night-time systolic blood pressure in diabetic patients: Dublin Outcome Study. Issue 7 (July 2015) - Draman, Mohd S.; Dolan, Eamon; van der Poel, Lelane; Tun, Tommy Kyaw; McDermott, John H.; Sreenan, Seamus; O'Brien, Eoin
Abstract : Objective: Diabetic patients exhibit a higher cardiovascular risk compared to people without diabetes. The use of ambulatory blood pressure monitoring (ABPM) is gaining popularity in this population. Night-time SBP has consistently been shown to be a potent predictor of cardiovascular risk in the normal population. We studied the predictive value of night-time ABPM in a cohort of diabetic patients. Research design and methods: At baseline, when not on antihypertensive medication, 11 291 patients (5326 men, mean age 54.6 years) underwent ABPM. Using a computerized national registry of death, mortality outcome was ascertained. Among 859 diabetic patients with a mean follow-up of 5.3 years, there were 74 deaths. Results: Compared to people without diabetes, those with diabetes had daytime and night-time SBP of 146.4 vs. 145.1 ( P  = NS) and 131.2 vs. 126.4 mmHg ( P  < 0.0001), respectively. As a consequence, more diabetic patients had a non-dipping night-time SBP profile (47.4 vs. 35.5%; P  =  < 0.0001). In a Cox proportional-hazards model, night-time SBP was an independent predictor of cardiovascular mortality in diabetic patients after adjustment for sex, age, smoking history, previous cardiovascular events, BMI and daytime SBP. The resultant hazard ratio for a 10-mmHg increase in night-time SBP for total cardiovascular, stroke and cardiac mortality was 1.32 (1.12–1.69), 1.95 (1.18–3.20) and 1.24 (0.99–1.56), respectively. Conclusion: Night-time SBP is a significant predictor of cardiovascular mortality in patients with diabetes.